Ultra-low-mass and small-radius white dwarfs made of heavy elements - Xia, Cheng-Jun; Huang, Yong-Feng; Li, Hong-Bo; Shao, Lijing; Xu, Ren-Xin (Frontiers in Astronomy and Space Sciences, 2023)
Seven possible ultra low-mass and small-radius white dwarfs have been recently identified with masses ranging from ∼0.02 M ⊙ to ∼0.08 M ⊙ and radii from ∼ 4270 km to 10670 km. The mass-radius measurements of these white dwarfs pose challenges to traditional white dwarf models assuming they are mostly made of nuclei lighter than 56 Fe. In this work we consider the possibility that those white dwarfs are made of heavier elements. Due to the small charge-to-mass ratios in heavy elements, the electron number density in white dwarf matter is effectively reduced, which reduces the pressure with additional contributions of lattice energy and electron polarization corrections. This consequently leads to white dwarfs with much smaller masses and radii, which coincide with the seven ultra low-mass and small-radius white dwarfs. The mass of the most massive white dwarf is effectively reduced and could possibly account for the sub-Chandrasekhar progenitors in underluminous Type Ia supernovae. The corresponding equation of state and matter contents of dense stellar matter with and without reaching the cold-catalyzed ground state are presented, which are obtained using the latest Atomic Mass Evaluation (AME 2020). Further observations are necessary to unveil the actual matter contents in those white dwarfs via, e.g., spectroscopy, asteroseismology, and discoveries of other ultra low-mass and small-radius white dwarfs.